DNA Methylation of Fluoxetine Response in Child and Adolescence: Preliminary Results - Martinez-Pinteño A; Rodriguez N; Blázquez A; Plana MT; Varela E; Gassó P; Lafuente A; Lazaro L; Mas S (Pharmacogenomics and Personalized Medicine, 2021)
Albert Martinez-Pinteño,1,* Natalia Rodriguez,1,* Ana Blázquez,2 Maria Teresa Plana,2 Eva Varela,2 Patricia Gassó,1,3 Amalia Lafuente,1,3,4 Luisa Lazaro,2– 5 Sergi Mas1,3,4 1Department of Basic Clinal Practice, Pharmacology Unit, University of Barcelona, Barcelona, Spain; 2Department of Child and Adolescent Psychiatry and Psychology, Institute of Neurosciences, Hospital Clinic de Barcelona, Barcelona, Spain; 3Clinical and Experimental Neuroscience Area, The August Pi i Sunyer Biomedical Research Institute (IDIBAPS), Barcelona, Spain; 4G04 Group, Centro de Investigación Biomédica en Red de Salud Mental (CIBERSAM), Carlos III Health Institute, Madrid, Spain; 5Department of Medicine, University of Barcelona, Barcelona, Spain*These authors contributed equally to this workCorrespondence: Sergi MasDepartment of Basic Clinal Practice, Pharmacology Unit, University of Barcelona, Casanova 143, Barcelona, E-08036, SpainTel +34 934024526Fax +34 934035881Email sergimash@ub.eduPurpose: The search for predictors of antidepressant response is gaining increasing attention, with epigenetic markers attracting a great deal of interest. We performed a genome-wide study assessing baseline differences in DNA methylation between Responders and Non-Responders.Patients and Methods: Twenty-two children and adolescents, receiving fluoxetine treatment for the first time, were classified as Responders or Non-Responders according to CGI-I score after 8 weeks of fluoxetine treatment. Genome-wide DNA methylation was profiled using the Illumina Infinium MethylationEPIC BeadChip Kit and analyzed using the Chip Analysis Methylation Pipeline (ChAMP).Results: We identified 21 CpG sites significantly (FDR< 0.05) associated with fluoxetine response that showed meaningful differences (Δβ> ± 0.2) in methylation level between Responders and Non-Responders. Two genes, RHOJ (Ras Homolog Family Member J) and OR2L13 (Olfactory Receptor family 2 subfamily L member 13), presented more than one significant CpG sites.Conclusion: Our findings provide new insights into the molecular mechanisms underlying the complex phenotype of antidepressant response, indicating that methylation at specific genes could be a promising biomarker that needs further replication in large cohorts.Keywords: epigenomics, epigenetics, DNA methylation, pharmacogenetics, antidepressants